Treatment outcomes among children treated for uncomplicated severe acute malnutrition: a retrospective study in Accra, Ghana. Issue 12 (12th August 2021) - Takyi, Abena; Tette, Edem; Goka, Bamenla; Insaidoo, Genevieve; Alhassan, Yakubu; Nyarko, Mame Yaa; Stepniewska, Kasia
Abstract: Objectives: The objectives of the study were to describe outcomes of children with uncomplicated severe acute malnutrition (SAM) attending community-based management of acute malnutrition (CMAM) treatment centres in Accra Metropolitan Area (AMA) and explore factors associated with non-adherence to clinic visits and defaulting from the treatment programme. Design: A retrospective cohort study analysing routinely collected data on children with uncomplicated SAM enrolled into CMAM in 2017 was conducted. Setting: Study was conducted at seven sites comprising Princess Marie Louise Children's Hospital, three sub-metropolitan health facilities and three community centres, located in five sub-metropolitan areas in AMA. Participants: Children with uncomplicated SAM aged 6–59 months, enrolled from community-level facilities (pure uncomplicated SAM, PUSAM) or transferred after completing inpatient care (post-stabilisation uncomplicated SAM, PSSAM), participated in the study. Results: Out of 174 cases studied (105 PUSAM, sixty-nine PSSAM), 56·3 % defaulted, 34·5 % recovered and 8·6 % were not cured by 16 weeks. No deaths were recorded. Mid-upper arm circumference (MUAC) increased by 2·2 (95 % CI 1·8, 2·5) mm/week with full compliance and 0·9 (95 % CI 0·6, 1·2) mm/week with more than two missed visits. In breast-feeding children, MUAC increased at a slower rate than in other children by 1·3 (95 % CI 1·0, 1·5) mm/week. Independent predictors of subsequent missed visits were diarrhoea and fever, while children with MUAC < 110 mm on enrolment were at increased risk of defaulting. Conclusion: A high default rate and a long time to recovery are challenges for CMAM in AMA. Efforts must be made to improve adherence to treatment to improve outcomes.